2021
DOI: 10.1073/pnas.2006482118
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular determinants of polymicrobial interactions in Fusobacterium nucleatum

Abstract: A gram-negative colonizer of the oral cavity, Fusobacterium nucleatum not only interacts with many pathogens in the oral microbiome but also has the ability to spread to extraoral sites including placenta and amniotic fluid, promoting preterm birth. To date, however, the molecular mechanism of interspecies interactions—termed coaggregation—by F. nucleatum and how coaggregation affects bacterial virulence remain poorly defined. Here, we employed genome-wide transposon mutagenesis to uncover fusobacterial coaggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(112 citation statements)
references
References 31 publications
0
112
0
Order By: Relevance
“…exposed Gal residues). For example, Fusobacterium nucleatum encodes multiple functionally characterized galactose-recognizing adhesins 91,92 and colonizes women with BV more often than women without BV 9,14 . The relative absence of sialic acids and exposure of galactose on the BV epithelium could therefore lead to improved colonization by F. nucleatum or other potential pathogens linked with BV.…”
Section: Discussionmentioning
confidence: 99%
“…exposed Gal residues). For example, Fusobacterium nucleatum encodes multiple functionally characterized galactose-recognizing adhesins 91,92 and colonizes women with BV more often than women without BV 9,14 . The relative absence of sialic acids and exposure of galactose on the BV epithelium could therefore lead to improved colonization by F. nucleatum or other potential pathogens linked with BV.…”
Section: Discussionmentioning
confidence: 99%
“…We next sought to examine the presence of several Fusobacterium virulence factors, of which pathogenicity has been proven in experimental studies, including genes encoding adhesin ( fadA, cbpF ), lectin ( fap2 ), and bacterial co-aggregation factor ( radD ) [12,13,29,30]. RadD is an autotransporter facilitating Fusobacterium’s interspecies interaction in polymicrobial biofilms [30], while CbpF inhibits CD4 + T-cell response through CEACAM1 binding and activation [31]. Genomic screening showed that fap2 was present and intact in the majority of genomes from both species (49/53), with disruptive mutations occurring in some isolates, such as the tumour-associated F. nucleatum animalis in P46 (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with Fap2, RadD and CmpA are considerably smaller adhesins that have predominantly been investigated for their roles in Fn's polymicrobial binding behavior (83,84). Potentially relevant to colorectal carcinogenesis as relates to colonic tumoral biofilms, Fn employs RadD to adhere to Clostridioides difficile and enhances C. difficile's extracellular polysaccharide production and biofilm formation (85).…”
Section: Enterotoxigenic Bacteroides Fragilismentioning
confidence: 99%